An exploration of content and drivers of online sustainability disclosure: A study of Italian organisations - Mura, Matteo (2020)
Authors would like to acknowledge the support of the research grant SPS Flagship ReIndustrialise Project, financed by EIT Climate KIC supported by EIT, a body of the European Union.